Improvement of alcoholic beverages technology for restaurant business - Kuzmin, Oleg; Mishurovskyi, Anatolii (My University, 2020)
The purpose of the work is to develop the scientific basis of antioxidant activity of water-alcohol infusions from plant raw materials and to identify the most promising plants as sources of natural antioxidants in the creation of alcoholic cocktails in restaurants.
Keywords: water-alcohol infusion; vegetable raw materials; antioxidant; restaurant; водно-спиртовий настій; рослинна сировина; антиоксидант; ресторан; кафедра технології ресторанної і аюрведичної продукції